Unik teologi på samisk grunn: Lars Levi Læstadius' teologi i nyere forskning - Elgvin, Lilly-Anne Østtveit (2016)
Unique Theology on Sámi Cultural Ground: Lars Levi Læstadius’ Sermons in Recent Scholarship This article has two main sections. The first section presents a brief survey and commentary of theological research on Læstadius since the mid1900s. The second section presents the method and findings of the author’s doctoral thesis on Lars Levi Læstadius’ spirituality. The article as a whole focuses on the need to take seriously the metaphorical language of Læstadius’ sermons as a necessary starting point of any investigation of his theology. Studying his linguistic and rhetorical style, as well as his exegetical principals, is argued to be both relevant and rewarding in order to understand his theology as it is reflected in the metaphorical universe of his sermons. An important outcome of the author’s approach has been the discovery of Læstadius’ theological affinity with the early church, and the importance of his closeness to Sámi language and culture for this.